An Optimization Model for Teaching Assignment based on Lecturer’s Capability using Linear Programming - Imam Eko Wicaksono; I Wayan Wiprayoga Wisesa (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
In the campus, the arrangement of teaching assignment for the lecturers have been the porblem encounterd by the management on the beginning of each semester. This process including assigning a class with suitable lecturer while adjusting the appropriate load for the lecturer. Such problem is non-trivial and can be considered as a linear system model. In this article, we try to solve the problem of teaching assignment using optimization model. We tried to maximize the capability of lecturers on particular subject while also considering their loads. Using branch and bound algorithm, the optimal solution were found and the problem are well solved.